x^2-(2/3)x-16/3=0

Simple and best practice solution for x^2-(2/3)x-16/3=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x^2-(2/3)x-16/3=0 equation:


x in (-oo:+oo)

x^2-((2/3)*x)-(16/3) = 0

x^2+(-2/3)*x-16/3 = 0

x^2-2/3*x-16/3 = 0

DELTA = (-2/3)^2-(-16/3*1*4)

DELTA = 196/9

DELTA > 0

x = ((196/9)^(1/2)+2/3)/(1*2) or x = (2/3-(196/9)^(1/2))/(1*2)

x = 8/3 or x = -2

x in { -2, 8/3 }

See similar equations:

| s^2=3+s(1-5s) | | -2(6x+9)+8= | | .5x+16=40 | | 5x+32=23 | | 9x+7-2x+4x-5+2y= | | x+9=-x+9 | | -(2+5)+(6z+1)=-2(z+1) | | 9-5(2n+10)=-1 | | 6+z=100 | | 4X+6=-20 | | ln(2x-1)+ln(3x+1)=1 | | 0.12y+0.08(y+6000)=1280 | | 5(3z-1)-4(z+4)=8(z+1) | | (7x-1)= | | -6.7(4t+6)-2.2(3t-5)= | | 1.2x+y=5 | | (3a-4)/2 | | -4(t-2)-(t+2)=11 | | 3a-4/2 | | 2x+3x=75 | | 396=(x+2)(x)(4) | | 11x^2+3=5(4x-3) | | b^3-2b^2-35b= | | x+3x+6x=350 | | -7p+2p-7=17+3p | | (6t+-4)=3(t+1)+3 | | s(9s+2)=7 | | 2x+-5=5 | | 8x+9y=72by-3 | | -7y-3y=30 | | 2t^2-87t-90=0 | | 11xsquared+3=5(4x-3) |

Equations solver categories